The Role And Implementation Of Zakat In The Development Of The Real Sector - Zaelani, Irwan; Arifudin, Opan; Sekhruri, Sekhruri (Yayasan Azka Hafidz Maulana, 2025)
This research is motivated by the fact that zakat is an obligation of Muslims and can be used as an effort to distribute wealth evenly. This can be seen from the many types of zakat; its use could be developed for the real sector. The next emphasis is on how Muslims themselves a strong desire must implement this system, and how it is managed so that it can be distributed evenly so that the goals can be achieved. The aim of this research is to determine the role and implementation of zakat in the development of the real sector. This research is qualitative research. The results of the research show that one of the ways to increase the income of mustahiq/dhuafa is the distribution of zakat which is carried out by providing business capital assistance for mustahiq/dhuafa. Because one of the sectors that needs attention and support is the real sector. As for large entrepreneurs, they have access to capital from many elements. The real sector has a very large role in absorbing unemployment rates, as well as increasing economic growth and social welfare. Apart from that, the performance of this sector also influences the performance of the financial or monetary sector.